Point of View Maslahah Mursalah Among Workers in Organizations: Exploring an Islamic Perspective with Humanistic Value - Prameswari, Dita; Nurcahyo, Satria Avianda; Damayanti, Adelia Ika; Rahayu, Indah; Fachrunnisa, Olivia (IJIBE (International Journal of Islamic Business Ethics), 2025)
This study aims to improve maslahah mursalah in organizations, measured from the perspective of today's active workers, and how they view maslahah mursalah in their respective workplaces. Humanistic leadership and work recognition are important and influential in implementing Islamic HRM in organizations. This study is motivated by several research gaps, especially the lack of research on maslahah mursalah in Islamic HRM. The method used in this study is quantitative research with a sample of 120 active workers in Grobogan Regency. Meanwhile, the sampling technique used is purposive sampling, with the criteria of working for a minimum of 2 years, aged 21-35 years old. Data analysis in this study is conducted with the SmartPLS 4.1 analysis tool. The study results show that humanistic leadership significantly influences work recognition, humanistic leadership significantly influences maslahah mursalah, work recognition significantly influences maslahah mursalah, and work recognition mediates the relationship between humanistic leadership and maslahah mursalah. On the other hand, there are findings related to the new concept of maslahah mursalah in organizations based on the perspective of today's workers who place more emphasis on knowledge, recognition, and reward.